2022
DOI: 10.3389/fgene.2022.827559
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Ferroptosis-Related Biomarkers in Septic Cardiomyopathy via Bioinformatics Analysis

Abstract: Septic cardiomyopathy (SCM) is a cardiac dysfunction caused by severe sepsis and septic shock that increases the risk of heart failure and death and its molecular mechanism remains unclear. Ferroptosis, a novel form of programmed cell death, has been reported to be present in the heart tissue of patients with sepsis, which demonstrated that ferroptosis may be a potential mechanism of myocardial injury in SCM. Therefore, we explored the role of ferroptosis-related genes (FRGs) in SCM and aimed to identify pivot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…From the published articles, we also found that Chen et al ( 61 ), Kang et al ( 62 ), Gong et al ( 63 ), Li et al ( 64 ), and Wang et al ( 65 ). similarly applied bioinformatics approaches to study the hub genes in SCM.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…From the published articles, we also found that Chen et al ( 61 ), Kang et al ( 62 ), Gong et al ( 63 ), Li et al ( 64 ), and Wang et al ( 65 ). similarly applied bioinformatics approaches to study the hub genes in SCM.…”
Section: Discussionmentioning
confidence: 58%
“…similarly applied bioinformatics approaches to study the hub genes in SCM. First and foremost, our studies with Chen et al ( 61 ), Kang et al ( 62 ), Li et al ( 64 ), and Wang et al ( 65 ) used the human SCM dataset GSE79962 as an experimental dataset, but we innovatively combined immune cell marker genes with SCM differentially expressed genes to identify the biomarker role of IRHG in SCM; Secondly, we also used MCODE to identify the central clusters of SCM differentially expressed genes to explore modules that play an important interaction in SCM and their involved pathways; Thirdly, different from the studies of Kang et al ( 62 ) and Gong et al ( 63 ), we also extracted human samples to verify the expression of target genes, and used ROC curves to analyze the diagnosticity of target genes for SCM. Finally, a miRNA-IRHG pair that is different from previous studies and has an immunomodulatory role in SCM was obtained: miR-222-3p/THBS1.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme cases of septic cardiomyopathy (SCM), a cardiac dysfunction caused by septic shock, can result in heart failure and mortality. Studies have indicated that ferroptosis may contribute to cardiac damage in patients with sepsis ( 72 ). Gong et al have used bioinformatics to pinpoint the roles of Cdkn1a, Ptgs2, Nfe2l2, Rela, and Vim5 in modulating ferroptosis in SCM ( 72 ).…”
Section: Ferroptosis and Cvdmentioning
confidence: 99%
“…Studies have indicated that ferroptosis may contribute to cardiac damage in patients with sepsis ( 72 ). Gong et al have used bioinformatics to pinpoint the roles of Cdkn1a, Ptgs2, Nfe2l2, Rela, and Vim5 in modulating ferroptosis in SCM ( 72 ). The inflammatory reaction is primarily regulated by islet cell autoantigen 69 (ICA69).…”
Section: Ferroptosis and Cvdmentioning
confidence: 99%
“…Immune cells recognize iron-depleted dead cells and initiate a chain reaction of inflammatory or specific immune responses [ 7 ]. Therefore, ferroptosis-associated genes (FAGs)have been recognized as promising diagnostic markers and potential therapeutic targets for sepsis [ 8 ], and prognosis models for the sepsis of children [ 9 ], or for sepsis-induced organ failure have been reported [ 10 ]. However, the value of FAGs in sepsis subtype identification and prognostic prediction remains unclear.…”
Section: Introductionmentioning
confidence: 99%